2018
DOI: 10.1016/j.biocon.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Sharks, rays and abortion: The prevalence of capture-induced parturition in elasmobranchs

Abstract: The direct impacts of fishing on chondrichthyans (sharks, rays and chimeras) are well established.Here we review a largely unreported, often misinterpreted and poorly understood indirect impact of fishing on these animalscapture-induced parturition (either premature birth or abortion). Although direct mortality of discarded sharks and rays has been estimated, the prevalence of abortion/premature birth and subsequent generational mortality remains largely unstudied. We synthesize a diffuse body of literature to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 66 publications
2
33
0
1
Order By: Relevance
“…The most significant impact due capture stress during the reproductive period is capture-induced birth or abortion, characterized by premature expulsion of an embryo (Adams et al, 2018), which could be confirmed by our results. This process has been reported to be common in numerous viviparous species at different stages of development resulting from capture and handling (Zagaglia et al, 2011;Schluessel, Giles & Kyne, 2015;Adams et al, 2018). However, our study brings the first detailed report combined with physiological alterations related to the phenomenon in an elasmobranch.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The most significant impact due capture stress during the reproductive period is capture-induced birth or abortion, characterized by premature expulsion of an embryo (Adams et al, 2018), which could be confirmed by our results. This process has been reported to be common in numerous viviparous species at different stages of development resulting from capture and handling (Zagaglia et al, 2011;Schluessel, Giles & Kyne, 2015;Adams et al, 2018). However, our study brings the first detailed report combined with physiological alterations related to the phenomenon in an elasmobranch.…”
Section: Discussionsupporting
confidence: 88%
“…Viviparous elasmobranchs are potentially vulnerable to reproductive disruptions of capture stress since their relatively long gestation periods increase the probability of post-release mortality or sublethal reproductive effects being caused by fishing while pregnant (Adams et al, 2018). The most significant impact due capture stress during the reproductive period is capture-induced birth or abortion, characterized by premature expulsion of an embryo (Adams et al, 2018), which could be confirmed by our results. This process has been reported to be common in numerous viviparous species at different stages of development resulting from capture and handling (Zagaglia et al, 2011;Schluessel, Giles & Kyne, 2015;Adams et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…A particularly concerning consequence of stress during the reproductive period is abortion, characterized by the spontaneous expulsion of an embryo before it is sufficiently developed to survive (Adams et al ., ). This type of trauma has already been reported for many viviparous elasmobranch species, with involuntary embryo loss at different stages of development because of capture and handling (Adams et al ., ; Rincon, ; Schluessel et al ., ; Zagaglia et al ., ). Thus, a better understanding of possible abortion consequences due to stress of capture is of utmost importance to understand potential effects on reproduction and recruitment in the following year and to develop successful conservation and sustainable management programs.…”
Section: Introductionmentioning
confidence: 97%
“…Viviparous elasmobranchs are particularly vulnerable to capture‐induced reproductive disruptions since their relatively long gestation periods increase the probability of post‐release mortality or reproductive consequences for females caught while pregnant (Adams et al ., ; Guida et al ., ). A particularly concerning consequence of stress during the reproductive period is abortion, characterized by the spontaneous expulsion of an embryo before it is sufficiently developed to survive (Adams et al ., ). This type of trauma has already been reported for many viviparous elasmobranch species, with involuntary embryo loss at different stages of development because of capture and handling (Adams et al ., ; Rincon, ; Schluessel et al ., ; Zagaglia et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation